2010
DOI: 10.4314/wajm.v28i5.55016
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel obstruction following perforation of the uterus at induced abortion

Abstract: BACKGROUND: Unsafe abortion is an important contributor to maternal morbidity and mortality. OBJECTIVE: To present a case of small bowel obstruction following perforation of the uterus at induced abortion. METHODS: A 36-year-old woman, presented at a private hospital, with abdominal pain and weight loss. She had full clinical assessment and laboratory investigations which indicated small bowel obstruction following perforation of the uterus at induced abortion, and was commenced on treatment. RESULTS: She was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Small bowel obstruction after uterine perforation has not been well documented, we were only able to find one case of bowel obstruction following uterine perforation, reported over 10 years ago [ 8 ]. A review found that in documented cases, clinical presentation and time of presentation following uterine perforation varies significantly [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Small bowel obstruction after uterine perforation has not been well documented, we were only able to find one case of bowel obstruction following uterine perforation, reported over 10 years ago [ 8 ]. A review found that in documented cases, clinical presentation and time of presentation following uterine perforation varies significantly [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others include hemorrhage, retained product of conception, infections, septic shock, anemia and reaction to abortificients used during procurement of the abortion. The high rate of morbidities and mortalities associated with abortions are mostly from above complications [2,5]. Long term complications include chronic pelvic pain, chronic pelvic inflammatory diseases, and increased risk of ectopic pregnancies, secondary infertility and psycho-social morbidities [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…To the victim, it compromises her health status and wellbeing, which could consequently affect the well-being of her family in particular and the community in general [5][6][7]. Complications resulting from induced abortion include uterine perforation, damage to the cervix and bowel perforation or prolapse.…”
Section: Introductionmentioning
confidence: 99%